Analisis Kinerja Sistem Transmisi Pada Mobil Hemat Energi Bono Kampar - Awaluddin, Ahmad; Syafri, Syafri; Anuar, Kaspul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In design a comfortable and safe car while driving, there are some things to watch out for, that isthe steering system, brake, and suspension. In this research, the author will analyze about the transmission system on the car Bono Kampar. Research on the transmission system begins with the search for data specification car Bono Kampar, after the vehicle specification data obtained, the next step is to find the center of car Bono Kampar, then calculate the speed of the vehicle on each gear ratio, from tooth 1, tooth 2, tooth 3 and tooth 4, calculate the net traction force on each gear ratio of 1 to 4, measure the fuel consumption, and measure the mileage at each gear ratio, and the analysis. From this research can be concluded what kind of fuel consumption and distance that can be reached in 1 litre of fuel by Bono Kampar car.Keywords: car, transmission system, speed car Bono Kampar, fuel consumption, car mileage in 1 litre of fuel